2015
DOI: 10.1073/pnas.1421535112
|View full text |Cite
|
Sign up to set email alerts
|

Two transcription factors, Pou4f2 and Isl1, are sufficient to specify the retinal ganglion cell fate

Abstract: As with other retinal cell types, retinal ganglion cells (RGCs) arise from multipotent retinal progenitor cells (RPCs), and their formation is regulated by a hierarchical gene-regulatory network (GRN). Within this GRN, three transcription factors-atonal homolog 7 (Atoh7), POU domain, class 4, transcription factor 2 (Pou4f2), and insulin gene enhancer protein 1 (Isl1)-occupy key node positions at two different stages of RGC development. Atoh7 is upstream and is required for RPCs to gain competence for an RGC fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
120
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 67 publications
10
120
0
Order By: Relevance
“…When RPCs exit the cell cycle, the post-mitotic precursor cells go through a series of changes of transcriptional regulatory programs. Atoh7 first appears in a subset of precursor cells to provide a competency state for RGC differentiation (Yang et al, 2003, Brown et al, 1998), and subsequently, Pou4f2 and Isl1 begin to express in some of these cells and direct them to differentiate into RGCs (Wu et al, 2015, Mu et al, 2008, Pan et al, 2008). However, the onset of Tbr1 expression in RGCs starts at a much later stage, around P0, suggesting that some of the early-born RGCs are likely to stay at an uncommitted state or in a protractedly long transcriptional program.…”
Section: Discussionmentioning
confidence: 99%
“…When RPCs exit the cell cycle, the post-mitotic precursor cells go through a series of changes of transcriptional regulatory programs. Atoh7 first appears in a subset of precursor cells to provide a competency state for RGC differentiation (Yang et al, 2003, Brown et al, 1998), and subsequently, Pou4f2 and Isl1 begin to express in some of these cells and direct them to differentiate into RGCs (Wu et al, 2015, Mu et al, 2008, Pan et al, 2008). However, the onset of Tbr1 expression in RGCs starts at a much later stage, around P0, suggesting that some of the early-born RGCs are likely to stay at an uncommitted state or in a protractedly long transcriptional program.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent differentiation of postmitotic RGCs is mediated by various TFs in monocular and binocular species (Kanekar et al, 1997; Wu et al, 2015). However, TFs selectively mediating contralateral or ipsilateral RGC cell fate and differentiation were not identified.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that Isl1 and Brn3b are not required for the specification of this cell type, but play a key role in their differentiation and survival (Mu et al, 2008;Pan et al, 2008;Sapkota et al, 2011;Li et al, 2014). However, it has recently been shown that ectopic expression of Isl1 and Brn3b in the Atoh7-null retina is sufficient for the specification of the retinal ganglion cell fate (Wu et al, 2015), suggesting that these transcription factors compose a minimally sufficient regulatory core for the retinal ganglion cell fate. These authors suggest that ectopic Isl1 and Brn3b can activate the native Isl1 and Brn3b genes, determining the retinal ganglion cell fate.…”
Section: Isl1 and Ganglion Cell Differentiationmentioning
confidence: 95%
“…These transcription factors sustain their own expression and no longer rely on the activator Atoh7. Then, Isl1 and Brn3b activate the gene expression program required for RGC differentiation (Wu et al, 2015). Brn3b binds to Isl1 within the C-terminal region forming a complex to regulate target genes in developing retinal ganglion cells (Li et al, 2014).…”
Section: Isl1 and Ganglion Cell Differentiationmentioning
confidence: 99%